Preliminary Phylogenetic Study of Bucephalandra (Schismatoglottideae: Araceae) - Nur Aina Afiqah, binti Abdul Halid (Universiti Malaysia Sarawak (UNIMAS), 2015)
Tribe Schismatoglottideae is one of the most species-rich and diverse aroids taxa in Borneo, with more than 250 species, of which over 95% are endemic. Schismatoglottideae contains a diverse group of rainforest terrestrial, litophytic or rheophytic herbs centred in Borneo. Bucephalandra (Araceae: Schismatoglottideae) is endemic to Borneo and known by its unique staminodes, with the presence of motile scale or shield-shaped staminodes situated at the interstice of the pistillate and staminate flower zones. Phylogenetic analyses of Bucephalandra were carried out in this study based on nuclear of Internal Transcribed Spacer (nrITS) and Megakaryocyte-associated tyrosine kinase (matK). Eight taxa were included in this study which also comprised the sister tribe, Cryptocoryne longicauda Becc. ex Engl. as the outgroup. Plant specimens were collected from respective localities. DNA was extracted from leaf samples, PCR amplified and sequenced. Analyses of both datasets with Maximum Parsimony, Maximum Likelihood and Bayesian Methods were carried out. Bucephalandra was revealed to comprise two clades.